Sharia Bank Product Development through Mudhrabah Investment - Trimulato Trimulato (Universitas Islam Negeri Raden Mas Said Surakarta, 2016)
Sharia banking now has a strong legal framework with the presence of law number 21 of 2008 on sharia banking in Indonesia. This regulation enforces sharia banking to develop products to achieve the targeted market share of 5%. In third-party fund products, more innovation is needed to attract people to entrust their funds in sharia banks. The visible data of mudharabah fund raising deposit products in March 2013 amounted to Rp100.746.000.000 and Rp115.728.000.000 in mudharabah deposits was visible on April 2014, which is an increase of less than 2% each month. This research uses a qualitative descriptive methodology, and is focused on fund raising products in shari'ah banking, particularly in the form of mudharabah investments for a definitive result. The results show that sharia banking requires innovative fund raising for third-party products, such as mudharabah investment products. These investments provide certainty of results despite using mudharabah and are based on the certainty that projector financing has been agreed by the sharia with the creditor banks. This investment product can be offered to both individuals and groups/collectives.Keywords: sharia banking, investment, mudharabah